Various Methods to Prepare High-Efficiency CaO Sorbents for Improved SO2 Capture Capacity. Issue 5 (2nd September 2016) - Moshiri, H.; Ale Ebrahim, H.; Nasernejad, B.
ABSTRACT: The reaction of calcium oxide with sulfur dioxide is one of the most important method for the flue gas desulfurization. However, the SO2 -capturing capacity of calcium oxide is low because of rapid pore blockage by solid products. In the present study, various methods for producing more porous solid lime structures were investigated. These methods consisted of microwave heating, freezing/thawing, adding some decomposable materials, and acetic acid washing of lime. The SO2 -capturing capacity of the produced sorbents were compared with the blank samples in a thermogravimetric analyzer at 850°C and 1000 ppm. The best performance was observed for the acid-washed lime. Finally, the experimental conversion-time profiles of natural and acid-washed limes were successfully predicted by modified grain model.